Concentrations of individual RNA sequences in polyadenylated nuclear and cytoplasmic RNA populations of Drosophila cells. - Biessmann, H (1980)
Steady state concentrations of individual RNA sequences in poly(A) nuclear and cytoplasmic RNA populations of Drosophila Kc cells were determined using cloned cDNA fragments. These cDNAs represent poly(A) RNA sequences of different abundance in the cytoplasm of Kc cells, but their steady state concentrations in poly(A) hnRNA was always lower. Of ten different sequences analysed, eight showed some four-fold lower concentration in hnRNA mRNA, two were underrepresented in hnRNA relative to the others. The obvious clustering of mRNA/hnRNA ratios is discussed in relation to sequence complexity and turnover rates of these RNA populations.